National Comorbidity Initiative - Psychogios, C; York, L (Published by Australian Institute of Health and Welfare & Printed by Pirion Printing, 2005)
The Australian Government, under the National Illicit Drug Strategy, allocated $9.7 million over five years to a National Comorbidity Initiative to improve service coordination and treatment outcomes for people with coexisting mental health and substance use disorders. One priority under this Initiative is to improve data systems and collection methods within the mental health and alcohol and other drug sectors to manage comorbidity more effectively. The Australian Government Department of Health and Ageing (DoHA) commissioned the Australian Institute of Health and Welfare (AIHW) to undertake this project to inform this priority area.
Drug Statistics Series Number 14
Keywords: Health -- Mental; Surveys and Survey Methodology -- Survey comparison; Surveys and Survey Methodology; Surveys and survey methodology; Health and wellbeing; Health; Surveys and Survey Methodology; Mental; Survey comparison; Health and wellbeing; Surveys and Survey Methodology